Prediction effect of ethanol molecules on doxorubicin drug delivery using single-walled carbon nanotube carrier through POPC cell membrane - Karimzadeh, Sina; Safaei, Babak; Jen, Tien-Chien (Elsevier, 2021)
The aim of this simulation was to investigate the effects of alcohol consumption on the efficiency of Doxorubicin (DOX) anticancer drug delivery system using Single walled carbon nanotube (SWCNT). To do so, first molecular dynamic simulations were performed to evaluate the effect of the presence of ethanol molecules on adsorption and encapsulation processes of DOX drug molecules in SWCNTs. The results showed that, in ethanol molecule-containing systems, the possibility of the encapsulation of drug molecules in SWCNT cavity was significantly decreased. Also, decrease of VdW interactions among drug molecules and SWCNTs were observed. To evaluate how SWCNT and DOX complex enters cell membrane in the presence and absence of ethanol molecules, a steered molecular dynamic simulation was performed to show the relationship and interactions between drug molecules and SWCNTs along the penetration into the lipid bilayer. Also, we investigated the stability of DOX molecules inside nanotubes in the presence and absence of ethanol molecules. We concluded that, in the presence of ethanol molecules in extracellular, more pulling force and longer time were required for DOX and SWCNT complex to penetrate cell membrane. It was also observed that due to the spontaneous encapsulation of ethanol molecules into SWCNTs, the adhesion of DOX molecules to the inner surface of SWCNTs was reduced and the possibility of its separation was increased. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: POPC; Doxorubicin; Drug delivery system; Ethanol; SWCNT; Molecular dynamic simulations